2022
DOI: 10.1038/s41419-022-04957-9
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of β-catenin-mediated negative feedback reinforces cAMP-induced neuronal differentiation in glioma stem cells

Abstract: Accumulating evidence supports the existence of glioma stem cells (GSCs) and their critical role in the resistance to conventional treatments for glioblastoma multiforme (GBM). Differentiation therapy represents a promising alternative strategy against GBM by forcing GSCs to exit the cell cycle and reach terminal differentiation. In this study, we demonstrated that cAMP triggered neuronal differentiation and compromised the self-renewal capacity in GSCs. In addition, cAMP induced negative feedback to antagoniz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 59 publications
1
8
0
Order By: Relevance
“…To clarify if CM combination has the same differentiation-inducing effect on glioma stem cells (GSCs) which are recurrence seeds of glioma, we evaluated the phenotype change, the transcriptome profile, and the profile of genes marked by H3K9ac and H3K14ac. First, we used two GSCs lines GSC1 and GSC11, both of which have been systematically validated to be characterized with stem cell properties [ 17 20 ]. Consistent with data from U87MG cells, CM-treated GSC cells were characterized by shrinking cell bodies and long synapse-like structure (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To clarify if CM combination has the same differentiation-inducing effect on glioma stem cells (GSCs) which are recurrence seeds of glioma, we evaluated the phenotype change, the transcriptome profile, and the profile of genes marked by H3K9ac and H3K14ac. First, we used two GSCs lines GSC1 and GSC11, both of which have been systematically validated to be characterized with stem cell properties [ 17 20 ]. Consistent with data from U87MG cells, CM-treated GSC cells were characterized by shrinking cell bodies and long synapse-like structure (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…GSC1 and GSC11 cell lines were derived from human GBM tumor samples and were characterized as reported previously [ 17 20 ]. Briefly, freshly resected GBM tissues were cut into small pieces, washed three times in DMEM/F12 medium (Gibco, Carlsbad, CA, USA), digested with trypsin (Gibco), triturated mechanically with surgical scissors, and filtered through a cell strainer (BD Biosciences, Franklin Lakes, NJ, USA).…”
Section: Methodsmentioning
confidence: 99%
“…The caspase recruitment domain (CARD) regulates signaling pathways related to innate immune responses, caspase activation, and inflammasome assembly. [ 25 ] CARD16 (also known as pseudo-ICE) comprises 97 amino acids containing a solitary CARD motif. [ 25 26 ] CARD16 can bind with the CARD of caspase-1 (CASP1) and negatively regulate CASP1 activity.…”
Section: Discussionmentioning
confidence: 99%
“…[ 25 ] CARD16 (also known as pseudo-ICE) comprises 97 amino acids containing a solitary CARD motif. [ 25 26 ] CARD16 can bind with the CARD of caspase-1 (CASP1) and negatively regulate CASP1 activity. [ 27 ] According to the literature, the loss of CASP1 can decrease the transcription levels of inflammatory factors and reduce the recruitment of pulmonary neutrophils.…”
Section: Discussionmentioning
confidence: 99%
“…Helena C found that GSCs-derived cells didn't undergo terminal cell cycle arrest and remain vulnerable to de-differentiation. When differentiation stimulation being withdrawn, they may return to GSC-like cells with proliferative potential (34)(35)(36).…”
Section: Discussionmentioning
confidence: 99%